Comparison of manual and automated palletizing of mixed size and weight box containers - Mital, Anil (International journal of industrial ergonomics, 1992)
In order to protect workers from injuries resulting from handling materials manually, it is frequently suggested that such activities should be automated wherever possible. For automation to be possible, it must meet two conditions: (1) automation should be technically feasible - that is proper equipment, grippers, material handling algorithms, etc. should be available and (2) it must be within the economic means of the company. Supporters of automation suggest that the cost of injuries is always higher than the cost of automation and the initial investment in equipment and support facilities can be recovered rather quickly. Such suggestions, however, ignore technical feasibility. The problem of palletizing boxes of mixed size and weight automatically is a rather difficult one and has, for a long time, lacked a practical solution. Recently, an expert system based algorithm was developed to palletize mixed weight and size boxes using industrial robots. This paper reports a case study undertaken to compare robotic palletizing, based on the proposed state of the art algorithm, with manual palletizing. Mixed weight and size boxes were used and performance and cost criteria were applied to evaluate the two alternatives.